The enzymology of enhanced hydrolysis within the biosulphidogenic recycling sludge bed reactor (RSBR) - Enongene, Godlove Nkwelle (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
The hydrolysis of complex organic heteropolymers contained in municipal wastewater to simpler monomers by extracellular hydrolytic enzymes is generally considered the rate-limiting step of the biodegradation process. Previous studies of the Recycling Sludge Bed Reactor (RSBR) revealed that the hydrolysis of complex particulate organics, such as those contained in primary sludge (PS), was enhanced under anaerobic biosulphidogenic conditions. Although the mechanism was not fully understood, it appeared to involve the interaction of sulfide and sludge flocs. The current study was conducted using a 3500 ml laboratory-scale RSBR fed sieved PS at a loading rate of 0.5 kg COD/m³.day and an initial chemical oxygen demand (COD) to sulfate ratio (COD:SO₄) of 1:1. There was no significant accumulation of undigested sludge in the reactor over the 60-day experimental period and the quantity of SO₄ reduced indicated that the yield of soluble products from PS was at least as high as those reported previously for this system (> 50%). In the current study, the specific activities of a range of extracellular hydrolytic enzymes (L-alanine aminopeptidase, L-leucine aminopeptidase, arylsulphatase, α-glucosidase, β- glucosidase, protease and lipase) were monitored in a sulfide gradient within a biosulphidogenic RSBR. Data obtained indicated that the specific enzymatic activities increased with the depth of the RSBR and also correlated with a number of the physicochemical parameters including sulfide, alkalinity and sulfate. The activities of α- glucosidase and β-glucosidase were higher than that of the other enzymes studied. Lipase activity was relatively low and studies conducted on the enzyme-enzyme interaction using specific enzyme inhibitors indicated that lipases were probably being digested by the proteases. Further studies to determine the impact of sulfide on the enzymes, showed an increase in the enzyme activity with increasing sulfide concentration. Possible direct affects were investigated by looking for changes in the Michaelis constant (Km) and the maximal velocity (Vmax) of the crude enzymes with varying sulfide concentrations (250, 400 and 500 mg/l) using natural and synthetic substrates. The results showed no significant difference in both the Km and the Vmax for any of the hydrolytic enzymes except for the protease. The latter showed a statistically significant increase in the Km with increasing sulfide concentration. Although this indicated a direct interaction, this difference was not large enough to be of biochemical significance and was consequently not solely responsible for the enhanced hydrolysis observed in the RSBR. Investigation into the floc characteristics indicated that the biosulphidogenic RSBR flocs were generally small in size and became more dendritic with the depth of the RSBR. Based on the above data, the previously proposed descriptive models of enhanced hydrolysis of particulate organic matter in a biosulphidogenic RSBR has been revised. It is thought that the effect of sulfide on the hydrolysis step is primarily indirect and that the reduction in floc size and alteration of the floc shape to a more dendritic form is central to the success of the process.
Keywords: Hydrolysis; Sewage sludge; Sewage -- Purification -- Anaerobic treatment; Water -- Purification -- Biological treatment